Hypothermia reduces seizure burden and improves neurological outcome in severe hypoxic–ischemic encephalopathy: an observational study. (22nd July 2016) - Guidotti, Isotta; Lugli, Licia; Guerra, Maria Pina; Ori, Luca; Gallo, Claudio; Cavalleri, Francesca; Ranzi, Andrea; Frassoldati, Rossella; Berardi, Alberto; Ferrari, Fabrizio
Abstract : Aim: To evaluate the antiepileptic effect of hypothermia and its association with neurological outcome in infants with moderate and severe hypoxic–ischemic encephalopathy (HIE). Method: We compared polygraphic electroencephalography monitoring and outcome data in 39 cooled and 33 non‐cooled term newborn infants, born between January 2005 and March 2013, and hospitalized because of signs of asphyxia and moderate to severe HIE. Results: Cooled newborn infants had fewer seizures (14/39 vs 20/33 p =0.036) and status epilepticus (7/39 vs 13/33, p =0.043), a lower mean duration of seizures (18mins vs 133mins, p =0.026), fewer administered antiepileptic drugs (median 0 vs 1, p =0.045), and more commonly a good outcome at 24 months (normal/mild motor impairment in 32/39 vs 16/33, p =0.003). Seizure burden (accumulated duration of seizures over a defined period) in cooled patients with both moderate (0.0 vs 0.1; p =0.045) and severe HIE (0.3 vs 4.9; p =0.018) was lower than in non‐cooled patients. Compared with non‐cooled patients, a good outcome was more common in cooled newborn infants with severe HIE ( p =0.003). Interpretation: Hypothermia has an antiepileptic effect in both moderate and severe neonatal HIE. The lower seizure burden in cooled newborn infants with severe HIE is more commonly associated with normal outcome at 24 months. What this paper adds: Cooled newborn infants with moderate and severe hypoxic–ischemic encephalopathy (HIE) have a lower seizure burden. In cooled newborn infants with severe HIE, normal outcome at 24 months is more common.